Geographies of Marketization in Higher Education: Branch Campuses as Territorial and Symbolic Fixes - Jana M. Kleibert (Economic Geography, 2021)
The role of higher education institutions as active agents of globalization and marketization remains relatively little explored. Economic geographic perspectives are particularly well placed to investigate globalizing higher education as an important economic sector, in addition to its supportive role in the knowledge economy. Drawing on political economic and cultural economic perspectives on marketization and geographic fixes, the study analyzes the motivations and spatial strategies for geographic expansion of universities through the establishment of branch campuses. Based on qualitative interviews with key decision-makers of English universities, I argue that (international) branch campuses enable a range of geographic fixes for higher education institutions: a territorial fix through the geographic expansion and construction of segmented markets and a symbolic fix through the relocation of campuses to places that promise reputational gains. The rapid growth of British branch campuses abroad and domestically (in the global city of London) involve substantial financial and reputational risks and as fixes constitute only temporary stabilizations. The conceptualization of symbolic fixes, in addition to territorial fixes, may enable a more nuanced understanding of the role of space in the construction of segmented, yet relational markets that combines intersecting political economic and cultural economic logics.
Keywords: 320; marketization; internationalization; territorial fix; symbolic fix; transnational education; international branch campus; United Kingdom